Directional emission from electrically injected exciton-polaritons in perovskite metasurfaces - Wang, Yutao (2023)
We present a new approach to achieving strong coupling between electrically injected excitons and photonic bound states in the continuum of a dielectric metasurface. Here a high-finesse metasurface cavity is monolithically patterned in the channel of a perovskite light-emitting transistor to induce a large Rabi splitting of ∼200 meV and more than 50-fold enhancement of the polaritonic emission compared to the intrinsic excitonic emission of the perovskite film. Moreover, the directionality of polaritonic electroluminescence can be dynamically tuned by varying the source-drain bias, which induces an asymmetric distribution of exciton population within the transistor channel. We argue that this approach provides a new platform to study strong light-matter interactions in dispersion engineered photonic cavities under electrical injection and paves the way to solution-processed electrically pumped polariton lasers.